Risk Reduction Tools For Education Internationalization - Aetdinova, Rasulya (2019)
The internationalization of education is attended with numerous risks. The paper aims to identify, analyze and evaluate tools of de-risking for education internationalization. Our study is based on the analysis of the activities of multicultural educational platforms. The research being done involved the study of the level of tolerance of students and teachers of Kazan Federal University (Russia), as well as an expert survey on the possibility of using multicultural educational platforms. The experience of using multicultural educational platforms by universities as a tool to reduce the risks of internationalization allows to extend our geographical scope through their activities in a rapidly changing environment and to raise graduates’ competitiveness.